PALLADIUM AND RUTHENIUM DERIVATIVES STABILISED BY BIS-SULFONE LIGAND - DEAK, Noémi; SEPTELEAN, Raluca; MORARU, Ionuț-Tudor; MALLET-LADEIRA, Sonia; MADEC, David; NEMES, Gabriela (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The synthesis and characterization of new palladium and ruthenium derivatives using the bis-sulfone 1,3-bis(4-methylphenyl)sulfonyl-5-tert-butylbenzene ligand is presented. The new compounds were characterized in solution by multinuclear NMR spectroscopy and for the palladium derivative, the molecular structure in solid state was also determined by single crystal X-ray diffraction. The work was completed with a DFT study in order to better understand the electronic effect in the stabilization of the new complexes containing bis-sulfone ligand.